6(x-2)/3=2(x+2)/5

Simple and best practice solution for 6(x-2)/3=2(x+2)/5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x-2)/3=2(x+2)/5 equation:



6(x-2)/3=2(x+2)/5
We move all terms to the left:
6(x-2)/3-(2(x+2)/5)=0
We calculate fractions
6x/()+(-(2(x+2)*3)/()=0
We calculate terms in parentheses: +(-(2(x+2)*3)/(), so:
-(2(x+2)*3)/(
We multiply all the terms by the denominator
-(2(x+2)*3)
We calculate terms in parentheses: -(2(x+2)*3), so:
2(x+2)*3
We multiply parentheses
6x+12
Back to the equation:
-(6x+12)
We get rid of parentheses
-6x-12
Back to the equation:
+(-6x-12)
We get rid of parentheses
6x/()-6x-12=0
We multiply all the terms by the denominator
6x-6x*()-12*()=0
We add all the numbers together, and all the variables
6x-6x*()=0

See similar equations:

| 70x-1+20+21=180 | | 5m+3=2m | | V(x+3)+4=10 | | X²+x+x³+1=0 | | 4x+17=4x | | 8/x-2/x=30 | | 45=54-t | | 28b+19=42b+12 | | 45x=56x | | 4x/5=10 | | 3x/5+x/9=1 | | 14b+23=35b+16 | | 2(x+7)+5=19 | | 100x^3=8 | | 24x+160=20x+180 | | -8p-3(3-4p)=2(p-6)-7 | | 8x+32=4(-2-4x) | | -17=w÷9 | | x-4/5x+1=x+5/x | | 4(3y-5)-77=-60 | | Z2-4z+2=0 | | 8x−5x−2=7 | | y+y+10=40 | | 4+6=-2(9x-5) | | a+2a+4a=78 | | 3/2(3x+5)=−24 | | 0.4x+0.1=0.7x-1.1 | | 200m-100m+53,075=53,075-175m | | x+119=x+77 | | 2a+4a+6a=78 | | 0.20(y-5)+0.04y=0.12y-0.1 | | x+77=x+119 |

Equations solver categories